Early Diagnosis and Monitoring of Adaptive Immune Response in a Cohort of Mild Mpox Patients During the 2022 Wave - Sara Caldrer; Silvia Accordini; Annalisa Donini; Natasha Gianesini; Andrea Matucci; Antonio Mori; Cristina Mazzi; Maddalena Cordioli; Evelina Tacconelli; Niccolò Ronzoni; Andrea Angheben; Chiara Piubelli; et al. (Microorganisms)
Our study wanted to describe the kinetics of serological and adaptive immune responses in mpox patients. Methods: Fourteen patients with laboratory-confirmed mpox were tested at different time points after the symptom onset. An immunofluorescence assay was performed to evaluate the seroconversion kinetics of specific IgA, IgM, and IgG. Moreover, the characterization of the adaptive immunological profile of T- and B-cells was performed. Results: The antibody kinetics revealed the faster and more effective seroconversion of specific IgA than IgM. Moreover, we detected an increase in Active memory B cells and CD8+ cells in the early phases of infection, and a reduction in CD4+ T-cells in the mpox patients with respect to the controls and found the presence of higher levels of Treg cells in the HIV+ patients in the early phase of infection. Conclusion: Our data highlight the relevance of specific IgA testing early after the symptom onset, suggesting a possible role as a marker in early diagnosis, especially in close contact subjects. Furthermore, the different maturation states of effector cells in HIV+ patients, together with high Treg levels, may lead us to better understand the role of MPXV-HIV co-infection and identify potential cellular markers to monitor the excessive immune activation involved in mpox disease progression.